Análise de custo-benefício na manutenção ou terceirização da frota de veículos oficiais: um estudo no campus da UFSM em Frederico Westphalen - Marco, Jardel Antonio de (2023)
Periodic renewal of an institution's vehicle fleet is necessary, given that after a certain period of use, vehicles begin to show wear and tear and mechanical problems, compromising the comfort and safety of their users, in addition to becoming uneconomical. This study aims to carry out a cost-benefit analysis between maintaining or outsourcing the fleet of official vehicles on the UFSM Campus in Frederico Westphalen. To carry out the analysis, the costs and advantages and disadvantages of each option were highlighted, considering the reality of the Campus, the situation of the fleet and the transaction costs in the case of outsourcing. The cost per kilometer traveled with the maintenance of the own fleet in 2022 was 17% more economical in relation to the possibility of leasing a vehicle with a driver. It was evident that there are great uncertainties related to the possibilities of contracting transport services to the Campus, in view of the lack of companies interested in the bids carried out, probably because it is an institution far from large centers, evidencing a possible case of specificity of service in the region. Thus, it is understood that renting a vehicle with a driver, if it becomes feasible in the locality, can be interesting to help in periods with high demand. In view of the analysis carried out, the advantage was proven to justify the maintenance of its own fleet and the search for the acquisition of new vehicles for the Campus, in view of the lowest cost in the long term and the certainty of availability to meet its demands.